PENGARUH TANGGUNG JAWAB, KOMITMEN MORAL DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI IKIP PGRI JEMBER - Semi Fariani (IKIP PGRI Jember, 2018)
Job performance is the result of a work achieved by an employee, through the totality of ability he has to achieve the goals of the organization. This research aims to know the influence of Responsibility, Moral Commitment and Discipline on Employee Performance. The type of research used is descriptive correlasional.jumlah sample in this study population is 35 people who are employees of IKIPPGRI Jember.teknik data collection used by researchers is a questioner. Data analysis used is descriptive statistic and inferential statistic analysis. The results of this study indicate that partially can be seen from the results of t-test that shows that the variable Responsibility (X1) has a significance level of 0.294, Moral Commitment variable (X2) has a significance level of 0.911, variable Discipline (X3) has a significance level of 0.251. Based on these calculations, it can be concluded that the partial responsibilities (X1), Job Performance (X2) and Discipline (X3) has a significant influence on Employee Performance (Y). Simultaneously variable Responsibility, Moral and Disciplinary Commitment significant effect on the dependent variable that is Employee Work Achievement (Y). which can be seen from the value (sig) F <? is 0.001 <0.05. Meanwhile, descriptive analysis shows that with responsibility, moral commitment and high discipline and applied by all employees of IKIP PGRI Jember, it will realize the work achievement in the form of achievement of all targets that have been set.